Audience awareness in elementary school students' texts. (2nd July 2022) - Skar, Gustaf B; Aasen, Arne Johannes; Kvistad, Anne H; Johansen, Marita B
Abstract : In this study, we investigated audience awareness characteristics in elementary school students' texts. To achieve this goal, we used a cross-sectional study design and sampled texts from 90 students in grades 1–3 (N = 270). These texts formed a corpus that was qualitatively analyzed by the research team. We used descriptive statistics to identify audience awareness patterns. Based on previous research, we expected to find considerable variation within and between grades. Therefore, we posed the following two research questions: (1) What characterizes audience awareness within grades 1–3? and (2) How does audience awareness develop between grades 1–3? We found that students used various rhetorical moves oriented toward the audience, such as greetings and closings, meta-text, explanations, and justifications. The results indicated that the students exhibited several characteristics related to audience awareness in all three grades. However, the variation within the grades was significant, while the variation between the grades was less pronounced.